Growth response of tissue culture-derived bamboo (Bambusa tulda Roxb.) Plantlets to sources and levels of inorganic nitrogen - Catherine C. Arradaza; Antoneth A. Modina; Arsenio D. Ramos; Rafonselle M. Moreno (Annals of Tropical Research)
Information on nitrogen nutrition of bamboo plants during the nursery stage is very limited. The study was conducted to generate more information regarding the nitrogen nutrition of bamboo (Bambusa tulda Roxb.) specifically to evaluate the effect of forms and levels of N on the early growth stage performance of tissue culture-derived bamboo plantlets and identify the best form and optimum level of nitrogen for bamboo plants during the nursery stage.